Combined Effect of Low Temperatures and Low Molecular Fraction (Below 5 kDa) of Cord Blood in Recovering Processes in Cartilage Tissue - Gulevsky, A. K.; Ivanov, Ye. G. (Problems of Cryobiology and Cryomedicine, 2009)
The influence of cryoeffect combined with the application of low molecular cord blood fraction (CBF) (below 5 kDa) on metabolism of polysaccharide components of the matrix and proteins of cartilage connective tissue after mechanical trauma has been studied. It has been established that cryoeffect, combined with intramuscular injection of CBF significantly stimulates the accumulation of main matrix components: hexosamine, hexuronic acids, hyaluronic acid, chondroitin sulfates and heparin as well as the most important structural proteins in cartilage regenerate, thereby providing a high level of regeneration stimulation of traumatized cartilage tissue.